A violência do rosto e a ética da responsabilidade na formação docente: um estudo a partir de Emmanuel Levinas - Grzibowski, Aline Caçapava Hernandes (2019)
The present dissertation intends to expose some influences and contributions from the field of Philosophy of Education to teacher education in Brazil, aiming at an ethical and sensitive reflection on the teaching knowledge, as well as its field of formation in a broad sense. The theory to be used as the background for the construction of this research will be that of the philosopher Emmanuel Levinas, who reflects themes such as Violence of the Face, Ethics of Responsibility / Alterity. For Levinasian thought, the other can not be constituted by the subject (ego), but the other or another comes to me and remains different. So, how do I understand that despite the existence of its inexhaustible alterity I am responsible for it? Levinas was not the only author to work the Alterity, however, he thought it in an odd way, to the point of making it the first philosophy that brings meaning to his work. It proposes to think from the ethics directed to the other. Thus, the reflection to be developed in this study arises around the construction of a sensitivity on the part of the teachers in relation to the signals given through their students' faces, aiming to open a proposition that contributes to a more human and sensitive teacher, open to dialogue and prepared to deal with possible conflicts arising from pedagogical practices. In this way, it is necessary that the faculty be prepared largely (since its formation) to deal with these signs and thus prevent possible situations of violence (especially face violence) occurring (or continue to occur) intra and extracurricularly. It is important that the set of professional knowledge mobilized and used by teachers in all their tasks be studied and taken into account, aiming, therefore, to help change this scenario of crisis that persists for several years. Therefore, it is necessary to develop a professional training that values teaching paradigms and that provokes teachers to be critical and reflective contributing to the effective improvement of the educational system as well as current educational policies.